Familial Hypertrophic Cardiomyopathy Related Cardiac Troponin C L29Q Mutation Alters Length-Dependent Activation and Functional Effects of Phosphomimetic Troponin I* - Li, Alison Y. (Public Library of Science, 2013)
The Ca(2+) binding properties of the FHC-associated cardiac troponin C (cTnC) mutation L29Q were examined in isolated cTnC, troponin complexes, reconstituted thin filament preparations, and skinned cardiomyocytes. While higher Ca(2+) binding affinity was apparent for the L29Q mutant in isolated cTnC, this phenomenon was not observed in the cTn complex. At the level of the thin filament in the presence of phosphomimetic TnI, L29Q cTnC further reduced the Ca(2+) affinity by 27% in the steady-state measurement and increased the Ca(2+) dissociation rate by 20% in the kinetic studies. Molecular dynamics simulations suggest that L29Q destabilizes the conformation of cNTnC in the presence of phosphomimetic cTnI and potentially modulates the Ca(2+) sensitivity due to the changes of the opening/closing equilibrium of cNTnC. In the skinned cardiomyocyte preparation, L29Q cTnC increased Ca(2+) sensitivity in a highly sarcomere length (SL)-dependent manner. The well-established reduction of Ca(2+) sensitivity by phosphomimetic cTnI was diminished by 68% in the presence of the mutation and it also depressed the SL-dependent increase in myofilament Ca(2+) sensitivity. This might result from its modified interaction with cTnI which altered the feedback effects of cross-bridges on the L29Q cTnC-cTnI-Tm complex. This study demonstrates that the L29Q mutation alters the contractility and the functional effects of the phosphomimetic cTnI in both thin filament and single skinned cardiomyocytes and importantly that this effect is highly sarcomere length dependent.